Analysis of Azithromycin adverse events in COVID-19 Patients reported to Iraqi Pharmacovigilance center in 2020 - Yasir A. Noori; Inam S. Arif; Manal M. Younus; Mohammed M. Mohammed (College of Pharmacy / Mustansiriyah University, 2022)
Azithromycin is an antibiotic that belongs to the macrolide family used in a wide variety of bacterial diseases. However, it has been proposed as a potential therapy for the treatment of SARS-CoV-2 pneumonia (off-label use) given for its antiviral and   immunomodulatory activity. Never-theless, its role in the treatment of COVID-19 remains unclear. Azithromycin has a well-characterized safety profile. However, its use outside the approved indication needs further follow up to ensure that the benefit-risk balance remains positive. One method to look for new/ changed safety information is through using the information component (IC025) value. IC025 is the lower limit of a 95% credibility interval for the IC. The credibility interval provides information about the stability of a particular IC value: the narrower the interval, the higher the stability. Objective: Study the submitted adverse events reports of Azithromycin to the Iraqi Pharmacovigilance center and compare the occurrence of these reported adverse events in Iraq to the internationally reported cases during 2020COVID-19 pandemic using IC025.   Methodology: The reported adverse events of Azithromycin to the national Pharmacovigilance database were studied qualitatively (age, gender and seriousness) and quantitatively (using IC025) as a measure of presence of a new/changed safety information related to Azithromycin.   Results: The total number of reports for Azithromycin were 419, female represent (43%) and male represent (55.8%), and the predominant age groups was from 45-64 years representing (41.1%). The most widely reported adverse events were gastrointestinal disorders (68%), cardiac disorders (14.1%), general disorders and administration site effect (6.9%), and investigations (Interfere with Lab tests) (5.7%). There were 96 drug-adverse reaction combinations. The IC025 value for the most widely reported adverse events showed a comparable value for ECG-QT prolonged (3.6/3.7), Arrhythmia (0.6/0.7). There was a decreased value for palpitation (0.5/0.9) and dyspnea (0.3/0.6). Tachycardia and increased liver enzymes showed an increased value of (2.0/0.1) and (0.5/0.1) respectively.   Conclusion: Using the IC025 was helpful in finding the increased reporting rate of adverse events compared to the background rate.